The impact of perioperative chemotherapy in patients with pancreatic adenosquamous carcinoma - Campbell, Brady; Habib, Joseph; Kinny-Köster, Benedict; Purchla, Julia; Franco, Jorge Campos; Putri, Aghnia Jolanda; Sahni, Shristi; Hewitt, D Brock; Sacks, Greg D.; Shubert, Christopher R.; Lafaro, Kelly J.; Burkhart, Richard A.; et al. (Surgery, 2025)
Background - Pancreatic adenosquamous carcinoma has historically poor overall survival, and the impact of perioperative chemotherapy remains unclear. We aimed to evaluate the impact of various chemotherapy regimens in patients with resected adenosquamous carcinoma. - Methods - Patients with resected adenosquamous carcinoma were identified from 3 high-volume programs between 2001 and 2022. We analyzed their clinicopathologic data and used Kaplan-Meier survival curves to assess the median overall survival and recurrence-free survival with 95% confidence intervals. Prognostic factors were assessed with a multivariable Cox-regression model adjusting for resectability status and Clavien-Dindo complications. - Results - Among 168 patients, cohorts of neoadjuvant chemotherapy (41, 24%) and upfront surgery (127, 76%) showed similar demographics and TNM staging. The median overall survival was shorter in the neoadjuvant chemotherapy cohort compared with the upfront surgery cohort (13 vs 21 months, P = .133). Median overall survival by treatment approach was no chemotherapy (4 months), only neoadjuvant chemotherapy (8 months), only adjuvant therapy (24 months), and both neoadjuvant chemotherapy and adjuvant therapy (17 months). Recurrence-free survival data (69 patients) showed upfront surgery had significantly longer recurrence-free survival compared with neoadjuvant chemotherapy (18 months vs 5 months, P = .046). Multivariable analysis showed adjuvant therapy was associated with improved overall survival (hazard ratio, 0.27; P < .001), whereas age ≥65 (hazard ratio, 1.79, P = .030) was associated with worse overall survival. - Conclusion - The outcomes of resected adenosquamous carcinoma remain poor. Patients receiving neoadjuvant chemotherapy exhibited shorter recurrence-free survival and median overall survival, suggesting minimal benefit of neoadjuvant chemotherapy in treating this aggressive cancer. Meanwhile, adjuvant therapy appears to be protective but requires further investigation.